IMPLEMENTASI KAIZEN DALAM MEMBANGUN BUDAYA KERJA INDUSTRI DI SMK (Studi Multi Situs di SMKN 2 Surabaya dan SMKN 1 Mojokerto) - Sucoko Sucoko; Amrozi Khamidi; Erny Roesminingsih; Andi Kristanto (Jurnal Manajemen Pendidikan, 2026)
Objective: This study analyzes the implementation of Kaizen in building an industrial work culture in Vocational High Schools (SMK), across three dimensions: training, habituation, and the reward and punishment system. Methods: A qualitative multiple-case embedded design was employed at two purposively selected sites, namely SMKN 2 Surabaya which has implemented the T-TEP program since 2014 and SMKN 1 Mojokerto which has implemented the N-KGTS program since 2022. The research was conducted over five months, from October 2025 to February 2026. Data were collected through in-depth interviews, direct observation, and document analysis, and analyzed using the Miles, Huberman, and Saldaña interactive model through first-cycle coding (initial coding) and second-cycle coding (pattern coding), followed by within-case and cross-case analyses. Results: Findings reveal that Kaizen training is sustained through multi-layered institutionalization covering formal legality, curricular integration, budget allocation, and industry-based instructor certification. Habituation builds student work character through three synergistic pillars of environmental engineering, formal institutional structures, and daily procedural routines that progressively shift internalization from compliance toward cultural ownership. A reward and punishment system grounded in a corrective-educative philosophy, reinforced through differentiated academic and industry recognition, sustains work culture consistency beyond momentary compliance.